БОШЛАНҒИЧ ТАЙЁРГАРЛИК БОСҚИЧИДА 11-12 ЁШЛИ БОКСЧИЛАРНИНГ БАЗАВИЙ ТЕХНИК ТАЙЁРГАРЛИГИ - Матжанов, Ж.М. (SCIENCE and SOCIETY, 2019)
The article examines the age-old features of the skills of young boxers to train in the initial stage of preparation and the step-by-step (backward, to the right, forward) movements of athletes. The competitor’s performance of the boxers was also analyzed and typical errors in attack technique and steps were identified.